2007
DOI: 10.1002/jmv.20843
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of hepatitis A in St. Petersburg, Russia, 1997–2003

Abstract: The molecular epidemiology of hepatitis A virus (HAV) strains circulating in the St. Petersburg and Karelia regions was studied during 1997-2003. Hepatitis A virus RNA was isolated from both clinical samples (stools or sera) and environmental samples (sewage water). RT-PCR was carried out using different primer pairs from the VP1/2A and VP1 genomic regions, the variable parts of the HAV genome. PCR products were sequenced and 306 nucleotides from the VP1/2A and 332 nucleotides from the VP1 region were used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…One sample from 2000 without travel information was found to be very similar to Russian strains from the same and the following year [Davidkin et al, 2007].…”
Section: Phylogenetic Analysis and Molecular Epidemiologymentioning
confidence: 91%
See 1 more Smart Citation
“…One sample from 2000 without travel information was found to be very similar to Russian strains from the same and the following year [Davidkin et al, 2007].…”
Section: Phylogenetic Analysis and Molecular Epidemiologymentioning
confidence: 91%
“…HAV RNA was isolated directly from stools, sera, sewage water and syringes, and RT-PCR was performed as previously described [Davidkin et al, 2007]. Syringes were washed with lysis buffer to obtain samples for RNA extraction.…”
Section: Rna Isolation and Rt-pcrmentioning
confidence: 99%
“…The latter confirms the presence of low herd immunity to the virus HA. Special studies of HA molecular epidemiology demonstrated, that isolates, related to the subtype IA, are the main circulating HA viruses in Russia, being a leading causative agent, ensuring its continued circulation in the low and high endemicity [12,13]. It was shown that viruses of this subtype have a high reproductive activity [14] and can be effectively distributed in every way as typical for infections with the fecal-oral transmission.…”
Section: Methodsmentioning
confidence: 99%
“…It is important to emphasize that all the major food outbreaks of HA have recently been associated with this subtype IA [15,16]. Long-term monitoring of circulating genetic variants of the virus HA in St. Petersburg revealed the introduction of new, previously not encountered types of pathogen [12], which gives reason to believe that covert circulation of the pathogen takes place among low-manifestation of the epidemic process. Probably the same conclusion can be drawn for other areas of the country.…”
Section: Methodsmentioning
confidence: 99%
“…There are several examples where molecular techniques such as RT-PCR and sequencing have been used effectively in outbreaks to definitely relate the source of infection (De Serres, 1999;Sanchez, 2002;Chironna, 2004;Arankalle, 2006;Tallon, 2008). The molecular epidemiological techniques also helped to report several outbreaks in major European cities among men who have sex with men (MSM) (Reintjes, 1999;Bell, 2001;Stene-Johansen, 2002) as well as in intravenous drug users (IVDUs) (Davidkin, 2007).…”
Section: Application Of Molecular Technique In Deciphering Outbreaksmentioning
confidence: 99%